Cardiac Dysrhythmias and Neurological Dysregulation: Manifestations of Profound Hypomagnesemia - Sagger Mawri; Edward Gildeh; Namita Joseph; Bobak Rabbani; Bryan Zweig (Case Reports in Cardiology, 2017)
Magnesium is the second most common intracellular cation and serves as an important metabolic cofactor to over 300 enzymatic reactions throughout the human body. Among its various roles, magnesium modulates calcium entry and release from sarcoplasmic reticulum and regulates ATP pumps in myocytes and neurons, thereby regulating cardiac and neuronal excitability. Therefore, deficiency of this essential mineral may result in serious cardiovascular and neurologic derangements. In this case, we present the clinical course of a 76-year-old woman who presented with marked cardiac and neurological signs and symptoms which developed as a result of severe hypomagnesemia. The patient promptly responded to magnesium replacement once the diagnosis was established. We herein discuss the clinical presentation, pathophysiology, diagnosis, and management of severe hypomagnesemia and emphasize the implications of magnesium deficiency in the cardiovascular and central nervous systems. Furthermore, this case highlights the importance of having high vigilance for hypomagnesemia in the appropriate clinical setting.